Observer-based H8 control on stochastic nonlinear systems with time-delay and actuator nonlinearity - Yin, YanYan; Shi, P.; Liu, F.; Reza Karimi, H. (Elsevier, 2013)
In this paper, an observer-based H8 controller is designed for a class of extended Markov jump systems subject to time-delay and actuator saturation nonlinearity. Gradient linearization procedure is employed to describe such nonlinear systems by several linear Markov jump systems. Next, a mode-dependent Lyapunov function is constructed for these linear systems, and a sufficient condition is derived to make them stochastically stable, and then, a continuous gain-scheduled approach is applied to design a continuous nonlinear observer-based controller on the entire extended nonlinear jump system. A simulation example is given to illustrate the effectiveness of developed techniques. © 2013 The Franklin Institute.